1991
DOI: 10.1177/002221949102400206
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Disorder and Specific Reading Disability: Separate but Often Overlapping Disorders

Abstract: Within a large (N = 182) heterogeneous sample of clinic-referred children with DSM-III-diagnosed attention deficit disorder (ADD), three behavioral subgroups were identified via cluster analysis of teacher ratings: 40% of the children had ADD with hyperactivity (ADDH), 30% had ADD with hyperactivity and aggressivity (ADDHA), and 31% had ADD without hyperactivity or aggressivity. Proportionally more girls were in the ADD-only subgroup. Over half the sample (n = 94) were poor readers, with 82 meeting discrepancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
0
7

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(137 citation statements)
references
References 16 publications
8
122
0
7
Order By: Relevance
“…We detected a significantly higher occurrence of specific learning disabilities and phonological deficits among patients with combined ADHD/DCD. Learning difficulties, particularly reading disability 19,20 with or without writing and spelling difficulties, 3 often accompany both ADHD and DCD. Specific language impairment (SLI) also occurs frequently in patients with DCD, probably on the basis of a dyspraxic deficit.…”
Section: Discussionmentioning
confidence: 99%
“…We detected a significantly higher occurrence of specific learning disabilities and phonological deficits among patients with combined ADHD/DCD. Learning difficulties, particularly reading disability 19,20 with or without writing and spelling difficulties, 3 often accompany both ADHD and DCD. Specific language impairment (SLI) also occurs frequently in patients with DCD, probably on the basis of a dyspraxic deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Attention deficit disorder may mimic or coexist with other types of learning disorders, such as reading disabilities (Dykman & Ackerman, 1991), anxiety disorders, mood disorders, and other medical conditions (Rostain, 1988). In addition, ADDers may experience fine motor disorders, such as illegible handwriting as well as other learning disorders related to information processing (Melini, 1987).…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…May mimic or co-exist with other types of learning disorders, such as reading disabilities (Dykman & Ackerman, 1991) May mimic or co-exist with anxiety disorders, mood disorders, and other medical conditions (Rostain, 1988).…”
Section: Add Characteristics Anticipated Consumption Impulsivity Outcmentioning
confidence: 99%
“…Critics of the temporal processing deficit hypothesis might suggest that it is not specifically "temporal" processing, but rather attention that is inefficient in individuals whose performance on the rapid sequential tasks was reviewed above. Attention-deficit disorder (ADD) does coexist with reading disability in a substantial proportion of cases (Dykman & Ackerman, 1991;Felton, Wood, Brown, Campbell, & Harter, 1987), although it has been shown that this is more often the case with dyseidetic or mixed/unspecific types than with dysphonetics (Felton & Wood, 1989).…”
Section: Caveats and Qualificationsmentioning
confidence: 99%